A Novel COL4A1 Mutation in a Neonate with Intrauterine Intraventricular Hemorrhage and Porencephaly - Jihyun Noh; Euiseok Jung; Ah Young Jung; Beom Hee Lee; Byong Sop Lee; Ellen Ai-Rhan Kim; Ki-Soo Kim (Korean Society of Neonatology, 2020)
Collagen type IV alpha 1 (COL4A1) plays an important role in construction of the basement membranes of all human tissues, especially vessels. Mutations in COL4A1 lead to various multisystemic dysfunctions, including hereditary porencephaly, hemorrhagic stroke, hemiplegia, cerebral small vessel disease, and nephropathy. In this study, we describe a neonatal case featuring a novel de novo COL4A1 mutation, manifesting as fetal intraventricular hemorrhage and porencephaly. This patient is one of the youngest to have been diagnosed with the most severe phenotype. Our experience may assist clinicians in the diagnosis and management of this extremely rare genetic condition.